Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Explore a wealth of knowledge from professionals across various disciplines on our comprehensive Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

Expand and simplify the following:

-3(2x-1)^2 + 12x^2

Can someone please show me their working of this so I can get my head around it!


Sagot :

Answer:

Hope that this is helpful.

Step-by-step explanation:

-3(2x-1)^2+12x^2

= -3[(2x-1)(2x-1)]+12x^2

=-3[2x(2x-1)-1(2x-1)]+12x^2

=-3(4x^2-2x-2x+1)+12x^2

=-3(4x^2-4x+1)+12x^2

=-12x^2+12x-3+12x^2

=(-12x^2+12x^2) +12x-3

=0+12x-3

=12x-3